Optimization of Medium Voltage Overhead Line Design for PT Algae Marine Life at PT PLN Kariango Customer Service Unit - Rolandi Tumpal Siregar (International Journal of Social Service and Research, 2023)
The addition of premium customers at PLN ULP Kariango has an impact on the electricity supply burden borne by PLN. This study uses an experimental research model. These designs will be tested and graded based on established standards. Data collection was carried out by observing and opening data specifications for electric power system equipment. Data analysis in this study used ETAP software. For Option 1 the SUTM design does not meet the technical requirements because there is a % power loss of 16.3 % and a % voltage drop of 31.1 %. For financial analysis, option 1 was not implemented because the technical requirements were not met. For the 2% option, the power loss of 46.2% does not meet the technical requirements. For financial analysis option 2 already meets the requirements. For option 3, the technical criteria for shrinkage is 10.87% and the voltage drop is 0.4%, which fulfills the technical requirements. For financial analysis, option 3 already meets the financial requirements. So that the results of the optimization of the three SUTM designs were chosen the best option 3 SUTM design.